Fabrication of a WO3 Conductometric Activated Thin Film Sensor for Resistance-to-frequency Conversion Based Sensing Application. Issue 1 (2nd January 2022) - Biswas, Bikram; Dey, Anup; Roy, Subhashis; Sarkar, Subir Kumar
Abstract : In this paper, we propose and experimentally evaluate the feasibility of incremental frequency change due to change in contact gas percentage, as a sensing parameter for WO3 based thin film ethanol detector. In the present work, an economic but accurate ethanol detection system has been realized along with a signal conditioning circuit where a timing resistance of a 555 timer is constituted by a WO3 based thin film sensor. The incremental resistance change due to the variation of gas concentration results in the change in frequency of the astable multivibrator. Finally, by measuring the frequency using an oscillator, the ethanol percentage can be estimated. The whole system is simple and can be realized with only a few hardware components. Further, accuracy has been enhanced using the Pd and Pt modified WO3 based thin film sensor.